Advances in Genetic Breeding of Rice with High Resistant Starch - Xueli YANG; Xuhua OU; Aoqiu FU; Wuming XIAO; Tao GUO; Yuelong LIN; Qianqi GUO; Guili YANG; Lijun MENG (Guangdong nongye kexue)
As a new type of dietary fiber, resistant starch can control blood sugar and cholesterol levels and improve intestinal health, and has become a research hotspot in the fields of functional food and crop genetics in recent years. Rice is an important food crop in China, and breeding rice varieties with high resistant starch is of great significance to improve the nutrition and health status of people who depend on rice as their staple food and meet the demand for healthy life in the future. The content of resistant starch in rice is mainly regulated by a few major starch synthesized genes and many minor genes, and the allelic combinations of different major genes also have significant effects on the content of resistant starch. At present, some rice varieties with resistant starch content as high as 10% have been cultivated in production, however, the increase of resistant starch content is often accompanied by the decrease of rice cooking taste quality, which seriously affects consumers' willingness to eat. It will be the focus and difficulty of future research to cultivate high resistant starch rice varieties with good taste. At the same time, breeding multi-functional rice with multiple compound functions (such as high resistant starch, high anthocyanin or low protein, etc.) is also a direction of resistant starch breeding in the future. Gene editing, gene pyramiding and other biotechnological breeding methods combined with traditional cross breeding can improve the breeding efficiency of starch resistant rice varieties. In this paper, the types of resistant starch in rice, the main genes related to biosynthesis pathway and the progress in breeding of high resistant starch rice were reviewed, and the focus and direction of future research were prospected, with an aim to provide some references for the breeding and industrialization of high resistant starch rice.